Taqlid, Ittiba’, Talfiq, dan Ijtihad dalam Ushul Fiqh - Alfan Ulya Ar-Rizq; Qolbil Auliya', Moh. Syafiq; Muttaqin, M. Imamul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Islam is known as a religion full of rules. There are many Islamic laws that emerged for the sake of human prosperity. On the other hand, changing times from year to year mean that Islamic law has to experience several problems as well. The problems that arise are usually based on differences in life patterns from time to time. In response to this, the ulama' are trying to make decisions to make it easier for Muslims so that deviations that lead to error do not occur. Researchers present this article in order to provide clarity on existing problems. In this way, it is hoped that readers will be able to know which legal steps are permitted and which steps are not permitted. This research was carried out using the literature study method by applying qualitative descriptive analysis techniques. As a result, most ulama' allow some methods of taking the law and prohibit several other methods. The decisions of these ulama' have of course been carefully calculated by taking into account human life from time to time.